The failure of the old islamic parties in Indonesian election: a study of the Partai Persatuan Pembangunan (PPP) 2019-2024 - Rofiq, Rofiq (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
The aim of this article is to explore the trend of declining votes for Islamic parties in contemporary Indonesia, both at the national and local levels. In particular, it examines the failure of the Partai Persatuan Pembangunan (PPP) in the 2024 elections. Some perspectives argue that the defeat of Islamic parties in Indonesia stems from their inability to adapt their ideological platforms, internal factionalism, and identity crises. Other views suggest that shifts in the ideological orientation of Islamic voters, who increasingly favor nationalist parties over Islamic parties, have also contributed to their electoral decline. This study employs a qualitative method with a sociological institutionalism approach, arguing that empirical sociological conditions played a decisive role in shaping the defeat of Islamic parties in the 2024 election. At least seven factors contributed to the failure of long-established Islamic parties to secure the support of Muslim voters. Chief among these was prolonged internal conflict, while additional factors included leadership crises, weak coordination and communication between central and regional legislative candidates, the loss of charismatic figures, misaligned endorsements of presidential and vice-presidential candidates, campaign strategies that failed to appeal to young voters, and inadequate financial and logistical resources.